SISTEM INFORMASI KEUANGAN BERBASIS WEB DI UMKM WARASIKO - Role, Adrianus Deo (JURSIMA, 2022)
MSME are productive businesses owned by individuals or business entities that meet the criteria of being a micro business. MSMEs also have an important role in building the economy. This Web-Based Financial Information System can help improve MSME performance. This study aims to find out how the application of information systems in managing and managing financial reports. This study uses the Waterfall method by following the various stages in it. In this study also testing was also carried out using the Black Box method. The results of this study indicate that there is still a lack of application of information systems to MSMEs and the quality of financial reports is still low, MSME owners still do not understand the use of the system and there is no socialization regarding the use of information systems to MSME owners. Keywords: : MSME, Information Systems, Financial Statements, Waterfall, Black Box.